1989
DOI: 10.2337/diab.38.7.942
|View full text |Cite
|
Sign up to set email alerts
|

Primary Association of HLA-DQw8 With Type I Diabetes in DR4 Patients

Abstract: DNA from 164 Caucasian type I (insulin-dependent) diabetic patients and 200Caucasian nondiabetic control blood donors were analyzed by the polymerase chain reaction technique for HLA-DR4 and the associated Dw and DQB subtypes of DR4. The DQw8 subtype of HLA-DR4 was associated with type I diabetes in all DR4 subgroups (DR4/3 and DR4/non-3). Dw subtypes of DR4 other than Dw10 did not confer additional association with type I diabetes. Thus, the DQ region appears to provide the primary major histocompatibility as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 24 publications
2
23
1
Order By: Relevance
“…The frequency of DQw8 is usually increased in patients compared with controls. This result has not, however, been confirmed in one other report [74].…”
Section: The Role Of Non-class II Mhc Genes In Susceptibilitycontrasting
confidence: 50%
See 1 more Smart Citation
“…The frequency of DQw8 is usually increased in patients compared with controls. This result has not, however, been confirmed in one other report [74].…”
Section: The Role Of Non-class II Mhc Genes In Susceptibilitycontrasting
confidence: 50%
“…Two other studies, however, have not found any significant difference between Dwl4 haplotypes and the other Dw DR4 haplotypes [74,107]. Dw subtypes of DR4 haplotypes apparently differ only at the DRB1 locus [31,39,113].…”
Section: The Role Of Non-class II Mhc Genes In Susceptibilitymentioning
confidence: 99%
“…The DQw8 allele of the DQBJ locus is increased in frequency in Caucasian and Black patients compared to controls in several studies (2,3,9,17,19,21,22,34,36). In Caucasians and Blacks, DQw8 is almost always in linkage disequilibrium with DR4 and A3 (7,9,(17)(18)(19)21).…”
mentioning
confidence: 96%
“…In Caucasians and Blacks, DQw8 is almost always in linkage disequilibrium with DR4 and A3 (7,9,(17)(18)(19)21). In general, there is a higher frequency of the DQw8 allele compared to the DQw7 allele in DR4-positive patients versus DR4-positive controls, indicating that DR4-linked susceptibility to type 1 diabetes is more likely to be controlled by genes within the DQ subregion than in the DR subregion.…”
mentioning
confidence: 97%
“…Both DR3 and DR4 are very strongly associated with IDDM: over 93% of IDDM cases have at least one of these alleles, compared to 43% of controls [11], with a significant increase in risk of DR3/DR4 heterozygotes [12][13][14]. HLA genotyping demonstrated later that the susceptibility of DR4 haplotypes is primarily due to linkage to the DQB1 alleles [15][16][17][18]. A strong association with homozygosity for particular amino acids other than Asp at position 57 was found [17,19,20].…”
Section: Introductionmentioning
confidence: 99%